ChemInform Abstract: The Germanides ScTGe (T: Co, Ni, Cu, Ru, Rh, Pd, Ag, Ir, Pt, Au) — Structure and 45Sc Solid State NMR Spectroscopy. Issue 12 (March 2015) - Heying, Birgit; Haverkamp, Sandra; Rodewald, Ute Ch; Eckert, Hellmut; Peter, Sebastian C.; Poettgen, Rainer
Abstract ScMGe (M: Co, Ni, Cu, Ru, Rh, Pd, Ag, Ir, Pt, Au) are obtained in pure form by arc‐melting of the elements.